2022
DOI: 10.1177/10442073221094803
|View full text |Cite
|
Sign up to set email alerts
|

Law Enforcement Officers: A Call for Training and Awareness of Disabilities

Abstract: Law enforcement officers (LEOs) are likely to encounter people with disabilities (PWD) during calls for service. These interactions sometimes escalate situations involving PWD and may result in arrest or death due to a lack of disability awareness among LEOs. The purpose of this study was to explore the current perspectives of LEOs regarding PWD and to identify the current training needs of LEOs regarding disability awareness and interactions with PWD. This study utilized two focus groups, consisting of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Seo et al (2021) found that co-response models outperformed other policing models because the presence of a mental health professional, such as a social worker, can effectively de-escalate the situation. Communities of color, the LGBTQIA community, and the disability community are killed at disproportionately high rates by police and thus may have cause to distrust police (Diamond & Hogue, 2022;Ghelani, 2022). Necessary changes will require new ways of developing strong police and community relationships, including accountability structures such as citizen review or advisory boards, clear and fair processes for reporting police misconduct, new strategies for diversion, and a greater emphasis on national accreditation through the Commission on Accreditation for Law Enforcement Agencies (CALEA) (A.…”
Section: Definition Of a Pswmentioning
confidence: 99%
“…Seo et al (2021) found that co-response models outperformed other policing models because the presence of a mental health professional, such as a social worker, can effectively de-escalate the situation. Communities of color, the LGBTQIA community, and the disability community are killed at disproportionately high rates by police and thus may have cause to distrust police (Diamond & Hogue, 2022;Ghelani, 2022). Necessary changes will require new ways of developing strong police and community relationships, including accountability structures such as citizen review or advisory boards, clear and fair processes for reporting police misconduct, new strategies for diversion, and a greater emphasis on national accreditation through the Commission on Accreditation for Law Enforcement Agencies (CALEA) (A.…”
Section: Definition Of a Pswmentioning
confidence: 99%